Akurasi Arah Kiblat Masjid di Ruang Publik - Anisah Budiwati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
This research explores the concept of understanding of mosque managers in the public space about the importance of facing the direction of Qibla. Samples Mosque located in the public space of the Hospital Jogja International Hospital, Adisutjipto Airport and Mall Plaza Ambarrukmo be proof of the tendency of pattern of understanding of managers of religious orders to face the direction of Qiblah correctly. By using qualitative analysis method and data collection method in the form of observation, interview and documentation, it is found that first, that understanding of mosque managers in public space at three places reflects the quality of life of Islami ie measuring to the expert so that the direction of qibla . Secondly, the accuracy of the direction of the mosque building in the public space in Sleman Yogyakarta is included in the category of accurate with the maximum reason for the 6 minute arc disturbance, where the direction of the largest deviation on the mosques is 0o 1 '20.8